2022
DOI: 10.1186/s13012-021-01177-1
|View full text |Cite
|
Sign up to set email alerts
|

Using theories and frameworks to understand how to reduce low-value healthcare: a scoping review

Abstract: Background There is recognition that the overuse of procedures, testing, and medications constitutes low-value care which strains the healthcare system and, in some circumstances, can cause unnecessary stress and harm for patients. Initiatives across dozens of countries have raised awareness about the harms of low-value care but have had mixed success and the levels of reductions realized have been modest. Similar to the complex drivers of implementation processes, there is a limited understand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 100 publications
0
16
0
Order By: Relevance
“…There has been increasing exploration into the use of theory broadly in de-implementation efforts [4,13]. Recent reviews have reported that de-implementation efforts have increasingly utilized classic theories, determinant frameworks, and implementation theories to support efforts to reduce LVC [10,14]. Research is inconclusive on the value of implementation science knowledge for understanding de-implementation [4,7,8,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There has been increasing exploration into the use of theory broadly in de-implementation efforts [4,13]. Recent reviews have reported that de-implementation efforts have increasingly utilized classic theories, determinant frameworks, and implementation theories to support efforts to reduce LVC [10,14]. Research is inconclusive on the value of implementation science knowledge for understanding de-implementation [4,7,8,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there has been a call for qualitative research to explore the complexities of de-implementation and how determinants differ depending on the type of LVC [1,5]. Building on previous work [14,23] this study aims to understand, (i) factors that sustain LVC, (ii) the magnitude of the problem (LVC), and (iii) factors that impact de-implementation processes. These aims are accomplished through an exploration of Choosing Wisely Interventions implemented in hospital and primary care settings.…”
Section: Introductionmentioning
confidence: 99%
“…12 Several literature reviews have explored barriers, enablers and interventions for deimplementation of low-value care. [12][13][14][15][16][17][18][19][20][21][22] Van Dulmen et al demonstrated that situation-specific knowledge of barriers and enablers is essential for designing tailored deimplementation interventions. 12 A systematic review conducted by Wang et al concluded that addressing patient, clinician and systemlevel barriers is necessary for successful deimplementation of low-value breast cancer surgery.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…14 Multifaceted interventions have the greatest potential to reduce low-value care [15][16][17][18] when interventions target tests individually, 16 involve patients in decision-making, 19 modify clinician environments, 20 address contextual factors 17 and are informed by behavioural change theories. 21 Identification of barriers and enablers as well as development of effective interventions have been highlighted as areas of deimplementation of low-value care that merit further research. 22 As part of global efforts to address low-value care, leading emergency medicine organisations have developed recommendations to reduce coagulation studies, 23 urine cultures, 24 25 blood cultures, 23 cranial CT in syncope, 26 cranial CT in head trauma, 23 cervical CT in neck trauma, 23 ankle radiographs in ankle trauma, 27 duplex lower extremity ultrasound in suspected deep vein thrombosis, 27 CT pulmonary angiography in suspected pulmonary embolism 27 and CT of the kidney-uretersbladder in suspected renal colic.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Too much focus is on end-stage joint replacement surgery and pain-relieving procedures or medications in the interim, at a significant cost to society and the individual. There is increased recognition across healthcare organisations and the field of musculoskeletal pain, that the overuse of procedures, testing, and medications constitutes low-value care which strains the healthcare system and causes unnecessary stress and harm for patients [ 7 , 8 ]. Ireland has substantial orthopaedic waiting list times that have recently been exacerbated by COVID-19 pandemic-related cancellations.…”
Section: Introductionmentioning
confidence: 99%